Analysis of Sport Tourism Potential in the Sanrobengi Island Area, Takalar Regency, South Sulawesi Province - Sahid, Masykur_; Bambang Budi Raharjo; Agus Raharjo (Universitas Negeri Semarang, 2025)
This research aims to: (1) To find out the condition of sports tourism on Sanrobengi Island; (2) Analyze the obstacles faced in the process of sports tourism development on Sanrobengi Island; (3) Analysis of the mapping of sports tourism potential in the Sanrobengi Island Area. This research is a qualitative analysis approach. The data collection techniques are observation, interviews, and documentation. The data validity technique uses source triangulation. The results of this study (1). Tourist facilities and infrastructure on Sanrobengi Island are in poor condition; (2) Cooperation has not been well established between tourism entrepreneurs and the Youth and Sports Tourism Office and the Government. The work program carried out by the Youth and Sports Tourism Office cannot run on Sanrobengi Island due to the ownership of the island. The services provided by tourism entrepreneurs and the community to tourists are good. Based on the results of the research, several conclusions were drawn that Sanrobengi Island has a very large potential for sports tourism to be developed where there are 80% of potential types of sports tourism such as marine sports, diving, futsal, snorkeling and sports events that can be developed. Advice to all tourism actors to always work together, build communication and carry out obligations and responsibilities as best as possible.